A Digital Green Banking Framework A Background Analysis for Fingerprint Approaches - Lojenaa, N.; Nawarathna, Ruwan D.; Suthaharan, S. (IRCICT 2018, Edhat International Ltd, 2018)
The fundamental activity of a bank is money related transactions. To perform such transactions, the banking service providers expect a valid and accurate signature from the customer to ensure correct identification and authentication. An accurate signature plays a significant role in security procedures of financial institutions. The customers as well as the bank employees face several problems due to the current manual signature system used in Sri Lanka. There are misuses of the manual system such as changing of the key parts as well as the slant of the signature over time. Fingerprint is one of the highly secured biometric systems. Therefore, fingerprint systems can be introduced for banking transactions to provide more secured services, because fingerprint never changes with age and get affected by any disease. It is nearly impossible to duplicate the fingerprint. This study proposes a digital banking framework to facilitate secure banking services using fingerprint authentication. A centralized fingerprint system may allow customers to access their bank accounts at any time from anywhere. The fraudulent withdrawal, unauthorized transactions, online financial forgeries, and other offenses can be easily trackable and reported to the relevant legislative authorities. Moreover, fingerprint scanners are not that expensive nowadays and installation can be done without any hassle. Fingerprint scanners can also be placed with the Automatic Teller Machine (ATM) because the bank can use it as an additional verification method for the customers, who forget their pin number. Fingerprint identification can be performed with the available standard pattern matching algorithms which are designed to extract minutiae points in each ridge and valley. A statistical study is conducted to show the effectiveness of the proposed framework. Furthermore, this will be a stepping stone towards green banking as manual records are replaced by digital records.
Keywords: Digital banking; Fingerprint analysis; Green banking; ATM; CDM